Ketika Digitalisasi Pemilu Menciptakan Ketimpangan Baru: Kasus Luwu Timur 2024: Kasus Luwu Timur 2024 - Sari Dwi Azanti; Ismah Tita Ruslin; Febrianto Syam (Spektrum, 2026)
The digitization of elections in Indonesia is often promoted as a way to increase efficiency and transparency. However, some academics question whether this shift truly supports equitable political participation. This study focuses on the Malili Subdistrict and examines how differences in digital access, literacy, and technology use contribute to unequal electoral participation in the 2024 East Luwu Regency Regional Election. The research uses a three-level digital divide framework—which considers access, skills, and usage—and analyzes participation through in-depth interviews with 16 purposively selected informants. The analysis reveals infrastructure disparities between the center and peripheral areas, resulting in a fundamental access gap (first-level). The disparities in digital literacy levels subsequently generate three groups: digital natives/savvy urban, digital natives/savvy with limited access, and digitally marginalized. This results in unequal technological utilization capabilities (second-level). This situation results in three patterns of participation: active digital participation, inert digital participation, and conventional participation that is either exclusive or creates disparities in the benefits or outcomes obtained (third-level). These findings emphasize that the digitization of elections, in the absence of a comprehensive strategy to confront the digital divide, has the potential to exacerbate democratic inequalities in electoral participation and to establish new stratifications that benefit groups with digital privilege.